The healthscaping approach: Toward a global history of early public health. Issue 1 (2nd January 2023) - Geltner, G.; Coomans, J.
Abstract: This article presents a modular, multidisciplinary methodology for tracing how different communities in the deeper past adapted their behaviors and shaped their environments to address the health risks they faced, a process also known as "healthscaping." Historians have made major strides in reconstructing preventative health programs across the pre- or non-industrial world, thereby challenging a common view of public health as a product of Euro-American modernity and biomedicine. However, these studies' general focus on cities and their reliance on archival and other documents that are more readily available in Euro-American contexts, limit the intervention's potential for rethinking the earlier history of public health comparatively, transregionally and on a global scale. A broader definition of health, additional sources and alternative methodologies allow us to expand research in and especially beyond urban Europe, promoting a global turn in health historiography that operates outside the seductive teleology of modernization, colonialism and imperialism.